2009
DOI: 10.1007/s12070-009-0027-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of deafmute patients: a study of ten years

Abstract: Present prospective study was conducted on 350 patients presenting with chief complaints of impaired hearing and delayed speech from 1996-2006. The aim of the present study was to fi nd out the prevalence of deafmutism in our area, the aetiology of childhood deafness and to ascertain the role of acoustic refl ex test (ART) for hearing screening considering brain stem evoked response audiometry (BSERA) as gold standard. A detailed history, clinical and other relevant systemic examination and investigations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…11 Singh et al, reported 10.80% perinatal cases while Kalsotra et al, reported only 4.60%. 6,7 In the present study postnatal causes contributes to 34% which is in accordance with various studies like Abolfotouch et al 10 In almost all the studies mentioned above the incidence of cases in postnatal period is almost same portraying same incidence of various infections in postnatal period amongst various groups of population. In the present study idiopathic causes contributed to 34% which is in accordance with Singh et al, (50.60%) and Elangos et al, (28.40%).…”
Section: Syndromic Hearing Losssupporting
confidence: 91%
See 3 more Smart Citations
“…11 Singh et al, reported 10.80% perinatal cases while Kalsotra et al, reported only 4.60%. 6,7 In the present study postnatal causes contributes to 34% which is in accordance with various studies like Abolfotouch et al 10 In almost all the studies mentioned above the incidence of cases in postnatal period is almost same portraying same incidence of various infections in postnatal period amongst various groups of population. In the present study idiopathic causes contributed to 34% which is in accordance with Singh et al, (50.60%) and Elangos et al, (28.40%).…”
Section: Syndromic Hearing Losssupporting
confidence: 91%
“…6 Singh et al, found in their study genetic causes of hearing loss to be 15.6%, non-genetic causes as 15.3% and idiopathic causes in 50.6% children. 7 Genetic causes of deaf mutism: The fact that genetic hearing loss is commonest cause of congenital and early hearing loss has also been reported by Wiley et al, 51.5%. 8 The findings in present study correlate well with those reported in literature.…”
Section: Etiologymentioning
confidence: 88%
See 2 more Smart Citations
“…Glusac, a Croatian poet said ''I am like a tree-trunk in a mountain deaf, and I might add dumb because I cannot speak for not hearing what is spoken'' [1]. The perception of hearing is very essential if one has to develop a means of communication.…”
Section: Introductionmentioning
confidence: 99%